Analysis of Zenith Sky Radiance in the Tropics: A Case Study of Chiang Mai and Nakhon Pathom, Thailand - Kanchanachat, Worapan; Masiri, Itsara; Serm Janjai (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Zenith sky radiance data collected at two sites: Chiang Mai station (18.78°N, 98.98°E) and Nakhon Pathom station (13.81°N, 100.04°E) in Thailand, were analyzed and used to develop a model. When analyzing the zenith sky radiance under all sky conditions, it was found that the diurnal variations of zenith sky radiance at both stations presented a similar pattern. The zenith sky radiance increased in the morning, peaked at noon, and decreased in the afternoon. The highest seasonal variation of zenith sky radiance occurred in the summer season (mid-February to mid-May) and the lowest value was in the winter season (mid-October to mid-February). The solar altitude, latitude of the location, and cloud cover affected variation of zenith sky radiance. For the modeling, the measurement data at Nakhon Pathom station were used for model development to estimate hourly zenith sky radiance under clear sky condition as a function of solar altitude. The hourly zenith sky radiance under clear sky condition data collected at Chiang Mai and Nakhon Pathom stations were employed to validate the accuracy of the model. The results showed that the measured and estimated hourly zenith sky radiance under clear sky conditions were in reasonable agreement, with root mean square error (RMSE) of 30.17% and mean bias error (MBE) of 7.48%. This model can be used to estimate zenith sky radiance data when measurement is not available and can be utilized to evaluate the maximum performance of solar energy applications.